2018
DOI: 10.1038/s41598-018-23555-4
|View full text |Cite
|
Sign up to set email alerts
|

Spin density wave instability in a ferromagnet

Abstract: Due to its cooperative nature, magnetic ordering involves a complex interplay between spin, charge, and lattice degrees of freedom, which can lead to strong competition between magnetic states. Binary Fe3Ga4 is one such material that exhibits competing orders having a ferromagnetic (FM) ground state, an antiferromagnetic (AFM) behavior at intermediate temperatures, and a conspicuous re-entrance of the FM state at high temperature. Through a combination of neutron diffraction experiments and simulations, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The lattice parameters are a = 10.0979 Å, b = 7.6670 Å, and c = 7.8733 Å with an obtuse angle of β = 106.298 • [9]. While crystallographically and electronically, as will be discussed in more details later, it is rather 3D, magnetically it can be viewed as a stack of ferromagnetically ordered planes with complex, but, presumably, weaker interplanar coupling [14].…”
Section: Experimental Situationmentioning
confidence: 99%
See 3 more Smart Citations
“…The lattice parameters are a = 10.0979 Å, b = 7.6670 Å, and c = 7.8733 Å with an obtuse angle of β = 106.298 • [9]. While crystallographically and electronically, as will be discussed in more details later, it is rather 3D, magnetically it can be viewed as a stack of ferromagnetically ordered planes with complex, but, presumably, weaker interplanar coupling [14].…”
Section: Experimental Situationmentioning
confidence: 99%
“…The material is known to have two metamagnetic tran- sitions [9,14], from a ferromagnetic (FM) to a spin density wave (SDW) at T 1 = 60 K, and back to a ferromagnetic state at T 2 ≈ 360 K (in this paper we apply the term SDW to any phase where spin polarization varies periodically in space; thus defined SDW can be either a spiral, or an amplitude SDW, wherein the magnitude of the magnetic moment varies continuously, or a combination of both). The long-range order is lost at T 3 = 420 K. The nature of the SDW phase will be discussed later, we will just mentioned that the neutron data can be fit equally well [14,15] by an amplitude SDW, where the spins are mostly aligned along c, or by a spin spiral, with the helical orientation, i.e., with the spins rotating in the ab plane. Either way, the spiral wave vector appears to be (0, 0, 0.29).…”
Section: Experimental Situationmentioning
confidence: 99%
See 2 more Smart Citations
“…The design, fabrication and study of novel compounds not found in nature, with an emphasis on interrelation between their electronic structure and physico-chemical properties, provide a promising basis for the development of technologically important materials [1][2][3][4][5][6][7]. Examples of such systems are transition-metal (TM) monogermanides with a cubic B20-type crystal structure, which are attractive for researchers in view of their exotic properties and hence, a variety of possible applications.…”
Section: Introductionmentioning
confidence: 99%